Assessment and Recognition of Refugee Credentials - Kohlenberg, Beatrice; Loo, Bryce (International Higher Education, 2020)
The current worldwide refugee crisis has provoked the examination of access and integration of refugees into higher education in host countries. The issues of access to, and assessment and recognition of, educational credentials are crucial for such access. Professional employment for those with higher education credentials is similarly challenging. Some initiatives are showing promise, particularly as UNESCO and the United Nations system in general begin to tackle the challenge on a global scale.